Transversality conditions for infinite horizon variational problems on time scales - Malinowska, A.B.
We consider problems of the calculus of variations on unbounded time scales. We prove the validity of the Euler-Lagrange equation on time scales for infinite horizon problems, and a new transversality condition. © 2010 Springer-Verlag.